The outcasts - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
Skandian outcasts Hal, Stig, and others do battle at sea against the Wolves and the Sharks, in the ultimate race across icy waters where not everyone thinks of the competition as playing.
"Companion to the bestselling Ranger's apprentice."
Keywords: Outcasts -- Fiction; Racing -- Fiction; Heroes -- Fiction; Friendship -- Fiction; Fantasy